O corpo e seus sentidos no teatro do oprimido: experiências contemporâneas em Arco-Íris do Desejo e Teatro Legislativo - Gabriela Serpa Chiari (2020)
This research consists of an investigation about the role of the body and the body work in the Theater of the Oppressed (TO), method created by Augusto Boal (1931-2009) as a starting point for overcoming the social, political and subjective oppressions of the practitioners. This objective is achieved through a contemporary critical and experimental approach to two modalities of TO: The Rainbow of Desire – Boal Theater and Therapy Method and Legislative Theater. This research seeks to increase the understanding of the body experience in the Theater of the Oppressed, aiming at body awareness and demechanization – relating them to concrete and continuous social actions, the main objective of the method's creator. The aim is to analyze the path that starts from the body – its consciousness, stimulus to the senses, enhancement of expressiveness – until the performance of actions in the subjective and institutional politics, which are present in these two modalities of the TO, through which an emancipation is sought in these two aspects.